The application of geospatial analyses to support an integrated study into the ecological character and sustainable use of Lake Chilwa - Rebelo, Lisa-Maria; McCartney, Matthew P.; Finlayson, C. Max (Elsevier, 2011)
Wetlands, which occupy a considerable proportion of Malawi, are an important resource for the rural-poor. In regions of low and erratic rainfall, they provide important opportunities for agriculture and fisheries and are often vital for food security. However, overutilization and some farming practices can result in environmental degradation and the loss of valuable ecosystem services. The Lake Chilwa wetland, a complex aquatic ecosystem comprising a shallow open water lake surrounded by marsh and floodplain grassland, is one of the most important wetlands in Malawi. Most of the 1 million people who live in the vicinity of the lake derive their livelihoods from the wetland. Increases in population in recent decades have increased the pressures on the wetland. In light of continued population growth, it is anticipated that some levels of resource use may be difficult to sustain in the long-term. Consequently, planning the use of wetland resources is a priority if the diverse benefits that local communities presently receive are to be sustained. Baseline wetland information is needed to determine appropriate sustainable management plans, as well as to identify limits to resilience. However, for many wetlands in southern and eastern Africa, these data are lacking, or not available to those who need them. This paper provides an overview of the distribution and characteristics of wetlands in Malawi. Using Lake Chilwa as an example, it illustrates how Earth Observation data, in combination with hydrometric and botanical data, can be used to provide information crucial for sustainable wetland management.